ANALYSE ET EVALUATION DES PARAMETRES ANTHROPOMETRIQUES ET DE LA PERFORMANCE PHYSIQUE CHEZ LES ATHLETES DE HAUT NIVEAU EN PERIODE DU JEUNE DU RAMADHAN - Said Aissa Khelifa (European Scientific Journal, ESJ, 2014)
Objective:Among the objectives of this research is to demonstratethe level of theorganism adaptation in relation to the effect of fasting (Ramadan). This is a prospective study to evaluate the effect of Ramadan fasting on some anthropometric parameters and physical performance indices in order to infer the credibility of the analyses performed during this month. It is the result of an inquiry from a field activity and it is based on the problematic activity field (coaches and athletes) and their questions in relation to this period when it will coincides notably with the internationals competitions. Its other objective is to contribute to increased knowledge of professional practice of athletic training. Methods: The study involved the analysis of someanthropometric parameters and indices of physical performance in elite athletes without changing the training program. The analysis required the creation of original tools to accurately locate the adaptation of the organism to the effects of fasting. The experiment was conducted in the laboratory with 23 volunteers athletes.The program is to analyse the parameters for five weeks before, during and after Ramadan period. Results:The analysis and discussion of research results have shown a positive physiological adaptation of athletes to the effect of fasting. This is evidenced by the parameters evaluated for this purpose, with some improvement in some parameters during the period of Ramadan. Conclusion: Generally, the deduction of the results of this research can be concluded that there is no major influence of fasting on the body during exercise. But the experimentationwas realized under very mild climatic conditions andthis should not be overlooked in times of extreme heat where the loss of water and salts may be important.